Vancomycin Resistance Is Maintained in Enterococci in the Viable but Nonculturable State and after Division Is Resumed - Lleò, Maria del Mar (American Society for Microbiology, 2003)
Stressed vancomycin-resistant enterococci (VRE) can activate a survival strategy known as the viable but nonculturable (VBNC) state and are able to maintain vancomycin resistance. During restoration of division they continue to express the vancomycin resistance trait. We suggest that VBNC enterococci may constitute further reservoirs of VRE and therefore represent an additional risk for human health.